Faktor – Faktor yang Mempengaruhi Muzaki terhadap Kepatuhan Membayar Zakat - Safira, Safira (Universitas Mercu Buana, 2023)
This study aims to determine the factors that influence the compliance of muzaki in paying zakat. The object of this research is Civil Servants (PNS) at the Head Office of the Directorate General of Customs and Excise Rawamangun who are Muslim. The data used is primary data with the technique of distributing questionnaires to respondents to respondents, namely Civil Servants (PNS) at the Head Office of the Directorate General of Customs and Excise Rawamangun. The data is processed using PLS. The results of this study indicate that the variable of worship has a positive and significant effect on compliance with zakat payments, while the variables of knowledge, wealth, income and government have no significant effect on compliance with zakat payments.